Current forest–savanna transition in Northern South America departs from Typical Climatic Thresholds (2023)
ABSTRACT:The forest–savanna transition is the most widespread ecotone in the tropics, with important eco- logical, climatic, and biogeochemical implications at local to global scales. However, the factors and mechanisms that control this transition vary among continents and regions. Here, we analyzed which factors best explain the transition in northern South America (Llanos ecoregion and north- western Amazon), where common thresholds on typical environmental factors (for example, mean annual precipitation (MAP), wet season precipitation) fail to predict it. For instance, savannas in the Llanos occur at MAP levels (> 1500 mm) which are typical of forests in other tropical regions. We examined the transition’s climate features, soils, and disturbance (fire frequency) spaces using re- motely sensed data. We used logistic generalized linear models to assess the effect of seasonal (sea- son length) and intra-seasonal (daily precipitation frequency and intensity) precipitation metrics during the dry season, soil silt content, and fire frequency, on the transition using canopy cover, tree cover, and the maximum Plant Area Volume Density as vegetation structure descriptor variables. Fire frequency and precipitation frequency were the most important variables explaining the transition. Although most fires occur in savannas, we found that a significant percentage of savanna pixels (46%) had no fires. This study indicates that the transition should be characterized regionally in response to biogeographic differences (for example, climatic space) among regions and continents. Our results highlight the importance of fire frequency and intra-seasonal precipitation in determining the transition in northern South America. Further- more, future studies should consider regional differences in the climatic space of forest and savanna to improve projections of global change impacts on these highly diverse ecosystems.